Medieval Plate Bracelets with Feline Images. Dating Issues - Elena A. Kroitor (Археология евразийских степей, 2022)
This paper deals with the dating of a narrow segment of medieval jewellery – plaque bracelets depicting feline faces. On the basis of the available material, two different positions have emerged in the scholarly environment to date. According to the main one, such jewelry dates back to the period of the Golden Horde and comes from Bolgar, Dzhuketau, Karasham and other sites of the Volga region. This point of view was supported by such authors as M.G. Kramarovskiy, N.F. Kalinin, K.A. Rudenko and other researchers. A different position is reduced to the extension of the chronological frames of usage these bracelets to the pre-Mongolian period, extending its geography to the borders of the Eastern European territory: for example, Otseleni-Deleni (Romania), Liubech (Ancient Rus) etc. This opinion was held by A.S. Gushchin, A.P. Smirnov and B.A. Rybakov. The paper presents the results of a study of materials from various chronological complexes and considers scientists' opinions on the issue of dating and geography of the origin of plaque jewelry with feline faces. The author concludes that the totality of finds dating back to an earlier time than the period of the Golden Horde provides strong grounds for expanding the chronological boundaries of the existence of bracelets of this type.